Sub-50-fs in-Band Pumped Tm, Ho-Codoped 'Mixed' Calcium Aluminate Laser - Lin,ZL; Chen,W; Zhang,G; Zhang,P; Li,Z; Chen,Z; Murray,RT; Loiko,P; Eremeev,K; Mateos,X; Griebner,U; Petrov,V (2025)
We report on a mode-locked Tm, Ho:Ca(Gd,Y)AlO4 laser in-band pumped by a Raman fiber laser at 1678 nm, generating 48-fs pulses slightly above 2μ m with an average power of 109 mW at 72.5 MHz.